La legislación aduanera en la nueva normalidad de la COVID-19 - Cosío Jara, Edgar Fernando (2021)
The COVID-19 pandemic has had an impact in health and the national economy, and in the legal sciences, one of the areas that had the most changes was customs law. When the state of emergency was declared as a result of the lethality of the pandemic, only cargo transportation was allowed in order to guarantee the pharmaceutic and food supply chain. Even though the international freight traffic contracted at the start ofthe pandemic, it later became one of the main engines for economic reactivation, and luckily, the Peruvian Customs Administration had started a legal and digital transformation process precisely in 2020. Throughout this essay, the author analyses this onslaught of changes in the Peruvian Customs Administration and its impact in the national legislation and economy.